A GREY LITERATURE REVIEW ON THE IMPACT OF SOCIO-ENVIRONMENTAL SUPPORT AND SOCIO-EDUCATIONAL PARTICIPATION TOWARDS STUDENTS’ WELLBEING - Deen Careemdeen, Jalal; Mahzan Awang, Mohd; Razaq Ahmad, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
This paper is developed from open access databases available online in order to have an overview of the concepts regarding socio-environmental and socio-educational participations towards student’s wellbeing. Databases that have been used to review including Directory of Open Access Journal (DOAJ), Google Scholar Educational Resource Centre (ERIC), Emerald, JSTOR-Journal Storage, Science Direct, Scopus, SpringerLink, Taylor and Francis and Sage Journals. Keywords for searching information are socio-environmental and socio-educational participations towards student’s wellbeing. Socio environmental factors have been found to play an important role in student participation in their learning and wellbeing. Given the role of socio environmental factors, this article conceptualizes several concepts on socio-environmental support, socio-educational participation towards students’ well-being. Conceptualization of this study is entirely developed based on sociological theories and secondary data but incorporating current literature reviews collected from different perspectives and sources. Different definitions and interpretations have been developed in conceptualizing socio-environmental support, socio-educational participation and students’ wellbeing by different scholars and organizations based on their different thematic motivations. In this study, socio-environmental support conceptualized as home environmental support, school environmental support, community environmental support and virtual environmental support for student involvement in learning and wellbeing. Socio educational participation conceptualized as parental involvement in student learning, student involvement in lesson activities and student involvement in extracurricular activities towards student educational achievement and their wellbeing. The student wellbeing conceptualized with five components, namely access to educational resources, enhancing soft skills, social skills, hard skills and hard skills.